Ugotavljanje dehidracije pri starostnikih, ki so bili obravnavani na nujni medicinski pomoči - Lešnik, Amadeus (Obzornik zdravstvene nege, 2015)
Introduction: The importance of adequate hydration cannot be stressed enough, but it is still a major problem for older people in hospital settings. The aim of study was to establish hydration status of the elderly (older than 65 years) living in long term care facilities in Maribor and its surroundings. Methods: In a retrospective study the values of markers of dehydration in 107 elderly aged over 65 years were assessed (70 women, average age 84.1 years and 37 men, average age 80.4 years). The elderly were referred to the Internal medicine emergency unit at the University medical centre Maribor in the period between November 1, 2013 to January 24, 2014. The data collected from medical info system were analysed. The criteria for dehydration included Serum sodium > 145 mmol/l, urea > 20 mg/ml or ratio urea/creatinine > 20 : 1. Results: An increased level of markers of dehydration was diagnosed in 73.8 % of the elderly included in the study, 35 participants meeting one criterion of dehydration, 39 participants two criteria and the remaining five meeting all three criteria. Discussion and conclusion: Results of the study show that the increased levels of markers of dehydration were not sufficient for accurate hydration assessment of the elderly. The diagnostic criteria used could easily either overestimate or underestimate the true hydration status. In the future research, more precise markers together with accurate evaluation of medical history and clinical signs are necessary to make an accurate assessment of the degree of dehydration in the elderly.
Keywords: dehidracija; dehydration; elderly; fluid balance; markers; označevalci; starostniki; tekočinsko ravnovesje